Perancangan Media Edukasi Hewan Terancam Punah Dan Hewan Punah Endemik Indonesia Untuk Pelajar Kelas 4 Sekolah Dasar Di Kabupaten Bandung - Banon Gilang; Sheila Mei Santi (ArtComm, 2020)
Endemic Indonesian animals are native Indonesian animals that cannot be found in other countries, that’s why their existence must be protected and studied by children, especially those with endangered status. However, the population of these animals is decreasing and even extinct. Not many people know about endangered animals that are endemic in Indonesia and extinct animals in Indonesia, especially in grade 4 elementary school in Bandung who have started to studying these animals. The knowledge about endangered animals and Indonesian endemic animals in schools is still ineffective and boring because the media to used is school textbooks which are dominated by text. Children's illustration books are a solution for elementary school. Data collection techniques used are interviews and questionnaires. The main media for the illustration book is "Ayo!! Mengenal Dunia Hewan" with supporting media : bookmarks, stickers, key chains, puzzles, and posters. The design was made to increase the knowledge of 4th graders elementary school about endangered animals and Indonesian endemic animals.